2019
DOI: 10.1021/acsomega.9b02438
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Study on the Determination of ppm-Level Concentration of Histamine in Tuna Fish Using a Dry Extract System for Infrared Coupled with Near-Infrared Spectroscopy

Abstract: Rapid and simple methods to determine histamine in tuna fish have been examined. A dry extract system for infrared (DESIR) was coupled with near-infrared spectroscopy in order to obtain the absorption of histamine in tuna fish at the ppm level. The result showed that the optimal extraction solvent for preparing DESIR samples was 75% methanol and boiling water (100 °C). Calibration equations were developed and tested by independent validation set samples. The calibration equation developed from boiling water as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…Over the last few years, NIRS has become a very common technique, frequently used to assess quality of food samples and adulteration including cocoa, coffee, milk or pork [ 8 , 10 , 11 , 12 ]. This method is also used to determine quality of fish and derived products: fatty acids in salmon oil, confirming authenticity of fish fillets and patties, histamine in tuna fish, sensory properties of Thai fish sauces, lipids in frozen fish, microbial content in salmon, distinction between wild and farmed sea bass [ 13 , 14 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Over the last few years, NIRS has become a very common technique, frequently used to assess quality of food samples and adulteration including cocoa, coffee, milk or pork [ 8 , 10 , 11 , 12 ]. This method is also used to determine quality of fish and derived products: fatty acids in salmon oil, confirming authenticity of fish fillets and patties, histamine in tuna fish, sensory properties of Thai fish sauces, lipids in frozen fish, microbial content in salmon, distinction between wild and farmed sea bass [ 13 , 14 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Calibration equations for these experiments were derived from the frozen fish pieces as well as ground samples by employing linear regression analysis for the wavelength region of 700-100 nm. The same authors have also demonstrated the ability of the NIR based method to rapidly determine in tuna, the content of histamine, a neurotransmitter responsible for the inflammatory response in humans [153]. In this study, the authors have coupled the dry extension system for IR (DESIR) with the NIR to determine the histamine in tuna at the ppm level.…”
Section: Nir Spectroscopy In Meat and Meat Products Fish And Seafoomentioning
confidence: 99%
“…Muscle foods, including meat and fish, are very important from the point of view of human nutrition and commercial activity worldwide [151]. There have been significant efforts, both from the industry and academia, on improving quality and quantity of the raw and processed muscle food types in recent years [151][152][153][154][155]. Accordingly, there have been increasing demands for the development robust and time effective monitoring techniques to track compositional and safety compliance issues as conventional chemical methods of meat quality assessment become more expensive and time consuming.…”
Section: Nir Spectroscopy In Meat and Meat Products Fish And Seafoomentioning
confidence: 99%
See 1 more Smart Citation
“…The identification of the adulteration of lamb, beef [ 23 ] and milk [ 24 ], the use of unauthorized preservation methods in fermented meat products [ 25 ], detection of spoilage bacteria in pork meat [ 26 ] and mislabeling of eggs in relation to production process [ 27 ] and honey [ 28 ] in relation to the geographical origin are just some examples. As for specific applications to fish and seafood, NIR spectroscopy has been successfully applied to qualitatively discriminate many products according to different authenticity features [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ], but also to quantify major, minor and trace matrix components [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. A short overview of the principal applications of NIR spectroscopy to the fish and seafood sector is provided in Table S1 .…”
Section: Introductionmentioning
confidence: 99%